PENGEMBANGAN MEDIA PEMBELAJARAN MIT APP INVENTOR BERPLATFORM ANDROID PADA MATERI STOIKIOMETRI DI KELAS X MIPA SMAN 7 KOTA BENGKULU - Sura Menda Ginting; Hermansyah Amir; Ruth Sinthia Ginting (ALOTROP, 2022)
This study aims to test the feasibility of learning media and determine student responses to the developed learning media. This type of research is research and development using a development model adapted from the Borg & Gall model, namely: 1) Potential and Problems, 2) Data Collection, 3) Product Design, 4) Design Validation, 5) Design Improvement, 6) Product Trial, 7) Product Revision, 8) Usage Trial, 9) Product Revision, and 10) Mass Product Manufacturing. But in this research, the research stages are limited to the sixth step namely the product trial stage. The research instruments used were interview sheet with chemistry teachers, questionnaires sheet to validate learning media and student response questionnaires to the developed media. The research was conducted at Bengkulu University and at SMAN 7 Bengkulu City with a research sample of 36 students of class X MIPA 4. From the research results obtained from learning media according to material expert validators is 88.75% and according to media expert validators is 90.90%. The average percentage of the feasibility of the learning media developed is 89.825%, so based on the results of validation by all validators, it is stated "Very Valid". Based on the results of product trials, the results of student responses in class to the MIT App Inventor learning media on stoichiometry material obtained a percentage of 89.27% ​​which was included in the very good category. The results of this study indicate that the MIT App Inventor learning media on stoichiometric material that has been developed is very feasible to use and feasible to be applied to the learning process